The Leptin Receptor Complex: Heavier Than Expected? - Wauman, Joris; Zabeau, Lennart; Tavernier, Jan (Frontiers in Endocrinology, 2017)
Under normal physiological conditions, leptin and the leptin receptor (ObR) regulate the body weight by balancing food intake and energy expenditure. However, this adipocyte derived hormone also directs peripheral processes, including immunity, reproduction, and bone metabolism. Leptin therefore can act as a metabolic switch connecting the body’s nutritional status to high energy consuming processes. We provide an extensive overview of current structural insights on the leptin-ObR interface and ObR activation, coupling to signaling pathways and their negative regulation, and leptin functioning under normal and pathophysiological conditions (obesity, auto-immunity, cancer, …). We also discuss possible cross-talk with other receptor systems on the receptor (extracellular) and signaling cascade (intracellular) levels.